Socialization Of The Dangers Of Drug Abuse For Mas Pp Students. Tarbiyah Islamiyah, South Labuhanbatu Regency - Aziddin Harahap; Hasmi Syaputra Harahap; Inés Aubone; Mohammed Mahdi Hassan; Nilofar Azmi (International Journal Of Community Service, 2022)
The purpose of the socialization activity on the dangers of drug abuse at MAS PP School. Tarbiyah Islamiyah in South Labuhanbatu Regency so that participants can understand the impact of drug use, both physical, psychological and socio-economic impacts. Socialization activities use participatory methods, lectures and discussions. The socialization activity was carried out on June 6, 2022 with the number of participants who took part in the socialization activity consisting of 50 sons and 65 students and 20 teachers located in the MAS PP hall. Tarbiyah Islamiyah, South Labuhanbatu Regency. For this reason, through socialization activities on the dangers of drug abuse, it is able to increase the understanding of MAS PP students. Tarbiyah Islamiyah, South Labuhanbatu Regency. regarding the types of narcotics, the impact of drug abuse from the physical aspect, psychological, educational, social and economic as well as ways of preventing and overcoming drug abuse among children and adolescents. For this reason, this socialization activity can fortify the younger generation as the nation's next generation, especially students at MAS PP. Tarbiyah Islamiyah, South Labuhanbatu Regency. from the dangers of drug abuse.